Fueling the Internet [computer power consumption]. - Perry, T.S (IEEE spectrum)
The author discusses power consumption of computers and their peripherals and household appliances which are supposedly switched off. The author examines the claims that the Internet is leading to growth in demand for electricity. The impact of this demand for power on the energy supply industry is also discussed